2011
DOI: 10.2174/187220811795655887
|View full text |Cite
|
Sign up to set email alerts
|

Recent Patents on the Synthesis and Application of Silica Nanoparticles for Drug Delivery

Abstract: Drug delivery systems are designed to improve therapy efficacy as well as patient compliance. This could be accomplished by specifically targeting a medication intact to its active site, therefore reducing side-effects and enabling high local drug concentrations. Silica nanoparticles have gained ground in the biomedical field for their biocompatibility and biodegradability, being themselves inert and stable, thus enabling a variety of formulation designs for application in the pharmaceutical industry. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Recently, it was found that silica particles carrying the antibiotic gentamycin could be immobilized at high silica dose in concentrated collagen hydrogels without modifying their fibrillar structure or impacting on their rheological behavior and increasing their proteolytic stability and mechanical stability. At the same time, gentamicin release from the nanocomposites was sustained over 7 days in comparison to free particles [27,36].…”
Section: Synthesis and Characterization Of Nanocomposites: In Vitro R...mentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, it was found that silica particles carrying the antibiotic gentamycin could be immobilized at high silica dose in concentrated collagen hydrogels without modifying their fibrillar structure or impacting on their rheological behavior and increasing their proteolytic stability and mechanical stability. At the same time, gentamicin release from the nanocomposites was sustained over 7 days in comparison to free particles [27,36].…”
Section: Synthesis and Characterization Of Nanocomposites: In Vitro R...mentioning
confidence: 90%
“…In this sense, silicified matrices exhibit increment in the rheological properties, enzymatic digestion occurred at a slower rate and cells seeded on silicified collagen matrices were able to adhere, proliferate and migrate within the scaffold [23][24][25][26]. In addition, silica nanoparticles have gained ground in the biomedical field for their biocompatibility and biodegradability, being themselves inert and stable, thus enabling a variety of formulation designs for application in the pharmaceutical industry [27][28][29][30].…”
Section: Mf Desimonementioning
confidence: 99%
“…We utilized silica nanoparticles (silica NPs) to anchor the CAS-CPT since they are highly inert and stable, exhibit excellent biocompatibility and allow for facile surface functionalization. 20 Briefly, amine-terminated silica NPs (300-nm; Corpuscular, Inc) were first activated with N,N′-disuccinimidyl carbonate in the presence of N,N-diisopropylethylamine, followed by reaction with the boc-deprotected CAS-CPT to obtain the NP-CAS-CPT (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…The research on application of carbon nanomaterials (CNMs) as multifunctional devices is eye-catching [7,8]. Among these materials, we focus on graphene, carbon-nanotubes, carbon-nanofibers, and fullerenes, which have capable appliances in the field of photocatalytic activity, electrochemical performances, bio-sensing, antibacterial coating and drug delivery [9]. Moreover, the interesting photoluminescence properties of CNMs, which are reported by several researchers will be discussed [10,11].…”
Section: Introductionmentioning
confidence: 97%